C3N5 photocatalyst with Janus homogeneous structure as well as preparation method and application of C3N5 photocatalyst

By introducing Janus homogeneous structure into C3N5-based materials, and using copolymerization reactions of NH4Cl and 1,2,4-triazole-3-thiol, C3N5 photocatalysts with cellular network and nanosheet-bound structure were prepared, solving the problem of low photocatalytic activity of C3N5 and achieving efficient charge separation and hydrogen generation.

CN119771460AActive Publication Date: 2025-04-08CHANGZHOU INST OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411697073.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-04-08
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The overall photocatalytic activity of C3N5-based materials in the field of photocatalytic energy conversion is limited by low charge separation efficiency, small surface area and lack of active sites, and the synthesis of heterojunction structures is difficult to control, resulting in carrier transfer being affected.

Method used

C3N5 photocatalysts with Janus homogeneous structure were prepared by using NH4Cl as a gas template, combined with copolymerization reaction of 1,2,4-triazole-3-thiol. The photocatalyst consists of a structure that combines a cellular network and nanosheets, with stacked holes inside to form a clear homozygous interface.

Benefits of technology

The Janus-C3N5 photocatalyst exhibited a significantly improved H2 precipitation rate under visible light irradiation, reaching 1712.4 μmol h-1g-1, which is much higher than the catalytic activity of bulk C3N5 and C4N4, and achieves effective charge separation and redistribution under the drive of the internal electric field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771460A_ABST
    Figure CN119771460A_ABST
Patent Text Reader

Abstract

Homojunction engineering has high performance in the application of photocatalysts, but still has a significant challenge in the establishment and adjustment of effective junction interfaces. In order to solve the problem, a novel Janus homogeneous structure photocatalyst is designed and constructed by integrating two different forms of triazolyl carbon nitride (C3N5). According to the invention, the nitrogen-rich cellular network C3N5 epitaxially grows on the carbon-rich C3N5 nanosheet with oversize and ultrathin thickness, so that a tight and wide interface contact area is formed. This arrangement enhances the built-in electric field (IEF) between the two forms of C3N5, facilitating faster directional transfer of photogenerated electrons and improved visible light collection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of photocatalytic energy conversion, and specifically relates to a C 3 N 5 Photocatalyst and its preparation method and application. Background Art

[0002] C 3 N 5 As a new type of nitrogen-rich carbon nitride, C-based materials have attracted extensive attention in the field of photocatalytic energy conversion due to their unique electronic and optical properties. However, their overall photocatalytic activity is greatly limited by low charge separation efficiency, small surface area, and lack of active sites. In order to improve the C-based materials, the photocatalytic activity of C-based materials has been greatly improved. 3 N 5 To improve the catalytic performance of semiconductors, various strategies have been adopted, including crystallization, heteroatom doping, defect removal, and heterostructure construction. Among them, heterojunction engineering is considered to be one of the most effective strategies to enhance carrier separation. However, junctions constructed between different semiconductors often suffer from random lattice mismatch, discontinuities, and defects, which can negatively affect carrier transfer.

[0003] Homojunction structures within single semiconductors have been proposed as a viable strategy to circumvent limitations. Similar compositions on both sides of the junction interface provide better lattice matching and chemical bond continuity. In addition, a built-in electric field can be established in the junction region, which enhances carrier separation and drives their migration to the active site. Carbon nitride-based photocatalysts have unique structural properties and offer great potential for the design and preparation of novel heterojunction photocatalysts. For example, Cui et al. developed a salt-assisted thermal polymerization method to prepare intermolecular homojunctions in carbon nitride nanosheets. Due to the intermolecular homojunction structure, this method achieves molecular-level contact, thereby enhancing the built-in electric field in carbon nitride (UTMCN). Therefore, compared with bulk gC 3 N 4 In comparison, the PHE rate of UTMCN is improved by 38.9 times. Other types of homojunctions have been found in carbon nitride-based photocatalysts by combining modified carbon nitride with pristine carbon nitride through doping with heteroatoms, structural vacancies, size control, and high crystallinity. However, most reported carbon nitride-based homojunctions are synthesized by direct thermal polymerization of two or more monomers or by assembling guest carbon nitrides on host carbon nitride, resulting in random junction structures. This randomness hinders catalytic performance and mechanism studies. Therefore, it is crucial to control the synthesis of homojunction photocatalysts with well-defined junction structures.

[0004] Janus heterostructure engineering offers a promising approach due to the distinct physical separation of the junction components and the ordered junction interface. However, current synthetic methods face significant challenges in designing, fabricating, and regulating regular Janus homojunctions in targeted carbon nitride-based photocatalysts. Recently, additive-mediated strategies have emerged as an effective means to shape carbon nitride-based nanostructures. In these approaches, additives can act as either gas templates to guide morphology development or dopants to modify the internal structure. Summary of the invention

[0005] The first object of the present invention is to provide: a C having a Janus homogeneous structure 3 N 5 The photocatalyst is composed of nitrogen-rich carbon nitride and has a structure combining a honeycomb network and nanosheets, with stacked holes inside.

[0006] The nitrogen-rich carbon nitride is a nitrogen-rich triazole group.

[0007] The photocatalyst forms a homojunction at the interface of the nanosheets and the honeycomb network.

[0008] The honeycomb network is a rough side, and the nanosheet is a smooth side.

[0009] The honeycomb network is mainly composed of nitrogen-rich and triazole groups, and the nanosheet is mainly composed of carbon-rich and triazole groups.

[0010] The second object of the present invention is to provide: a C having a Janus homogeneous structure 3 N 5 A method for preparing a photocatalyst. The purpose is to use NH 4 Cl as a gas template to prepare C with Janus structure 3 N 5 Based nanomaterials. 4 Rapid pyrolysis of Cl and copolymerization of 1,2,4-triazole-3-thiol to form two oriented gC 3 N 5 Nanomaterials integrated to form Janus-C 3 N 5 The specific steps include:

[0011] Step 1: Grind and mix triazole mercaptan and ammonium chloride, and rapidly pyrolyze the ammonium chloride to obtain a photocatalyst precursor;

[0012] Step 2: Transfer the photocatalyst precursor obtained in step 1 to a covered ceramic crucible for calcination.

[0013] In the step 1, the triazole thiol is 1H-1,2,4-triazole-3-thiol (3-ST), and the added amount is 1-5 g; 10-20 g of ammonium chloride is added, and the grinding time is 20-40 min.

[0014] In the step 2, the calcination conditions include: a heating rate of 1-3°C min-1, a temperature of 500-600°C, and a calcination time of 1-5h, preferably 4h.

[0015] The third object of the present invention is to provide: a C having a Janus homogeneous structure 3 N 5 Application of photocatalysts in energy conversion and photocatalysis.

[0016] Beneficial Effects

[0017] Photocatalyst Janus-C of the present invention 3 N 5 The Janus-C nanosheets have two different morphologies: ultrathin nanosheets (smooth side) and honeycomb networks (rough side). The nanosheets are mainly composed of carbon-rich triazole carbon nitride, while the honeycomb networks are mainly composed of nitrogen-rich triazole carbon nitride. This configuration leads to an enhanced internal electric field (IEF) between these different structures. Under visible light irradiation, Janus-C 3 N 5 H 2 The precipitation rate reached 1712.4 μmol h- 1 g- 1 , than block C 3 N 5 (306.8 μmol h- 1 g- 1 ) is about 5.58 times higher than that of bulk C 4 N 4 (121.2 μmol h- 1 g- 1 ) is 14.1 times higher. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 :(a)Janus-C 3 N 5 Schematic diagram of the preparation process; (bc) SEM micrographs; (de) TEM images, (f) dark field STEM images and their corresponding (gh) elemental mapping (c, N) images; (i) Janus-C 3 N 5 The yellow dashed rectangle highlights the rough side, the red dashed rectangle indicates the smooth side, the white dashed circle marks the pores, and the white solid arrow indicates the area of ​​the pore line EDS scan.

[0019] Figure 2 :Janus-C 3 N 5 Proposed reaction pathway for sample formation.

[0020] Figure 3 :(a)Janus-C 3 N 5 -1h, (b) Janus-C 3 N 5 -2h, (c)Janus-C 3 N 5 -3h and (d) Janus-C 3 N 5 SEM images of the samples.

[0021] Figure 4 :Janus-C 3 N 5 -1h, Janus-C 3 N 5 -2h, Janus-C 3 N 5 -3h and Janus-C 3 N 5 XRD patterns of the samples.

[0022] Figure 5 :(a) Block C 3 N 5 , Block C 3 N 5 and Janus-C 3 N 5 XRD patterns; (bd) FT-IR spectra; (e) Janus-C 3 N 5 C1s core-level XPS spectra and (f) N 1s core-layer XPS spectra at different etching times; (g) bulk C 3 N 5 and Janus-C 3 N 5 Structural model representation and (h) solid-state 13C spectrum of the sample.

[0023] Figure 6 :Bulk C 3 N 5 Static water contact angle measurements.

[0024] Figure 7 :Bulk C 3 N 5 Static water contact angle measurements.

[0025] Figure 8:(af)Janus-C 3 N 5 Static water contact angle measurements.

[0026] Fig. 9 :Different samples Janus-C 3 N 5 -1h, Janus-C 3 N 5 -2h, Janus-C 3 N 5 -3h and Janus-C 3 N 5 XPS spectrum survey of samples.

[0027] Fig.10 :(a)Janus-C 3 N 5 and bulk-C 3 N 5 C1s core-level XPS spectra of the samples at different etching times and (b) N 1s core-layer XPS spectra.

[0028] Fig.11 :Sample (a) Janus-C 3 N 5 and (b) bulk-C 3 N 5 Surface C and N compositions of different samples after Ar ion etching process (0s, 15s and 30s).

[0029] Fig.12 :(a)N 2 Adsorption-desorption isotherms, insert: photos showing different samples; (b) pore size distribution derived from the isotherms; (c) EPR spectrum; (d) UV-vis absorption spectrum; (e) schematic diagram of the band structure; (f) UPS spectrum; (g) photocurrent response spectrum; (h) EIS-Nquist diagram; (i) bulk-C 3 N 4 、bulk-C 3 N 5 and Janus-C 3 N 5 Steady-state PL spectra.

[0030] Fig.13 :Block C 3 N 4 , Block C 3 N 5 and Janus-C 3 N 5 Band gap energy of the samples.

[0031] Fig.14 :(a) Block C 3 N 4 , Block C 3 N 5 and Janus-C 3 N 5 H 2 Separation rate; (b) Janus-C 3 N 5 Recyclable performance in terms of hydrogen release; (c) Janus-C 3 N 5 Compared with other reported C 3 N 5 H-based photocatalysts 2 Comparison of release rates.

[0032] Fig.15 :Block C 3 N 4 , Block C 3 N 5 and Janus-C 3 N 5 Photocurrent response and time-resolved PL decay spectra of the samples.

[0033] Fig.16 : Schematic diagram of charge transport driven by potential difference.

[0034] Fig.17 :CN-C 3 N 5 The charge density difference (yellow and blue represent charge accumulation and loss, respectively).

[0035] Fig.18 :CC 3 N 5 The charge density difference (yellow and blue represent charge accumulation and loss, respectively).

[0036] Fig.19 :(ac) Carbon-rich C 3 N 5 (cC 3 N 5 ), nitrogen-rich C 3 N 5 , Compound C 3 N 5 The work function and state density (df) of CC 3 N 5 and NC 3 N 5 Schematic diagram of the internal electric field formation and charge transport mechanism. DETAILED DESCRIPTION

[0037] Reagents and materials

[0038] 1H-1,2,4-Triazole-3-thiol (C 2 H 3 N 3 S, ≥97.0%), melamine (C 3 H 6 N 6 , ≥99.0%), potassium hexachloroplatinate (K 2 PtCl 6 , ≥98.0%), ammonium chloride (NH 4 Cl, ≥99.0%) and triethanolamine (TEOA, C 6 H 15 NO 3 , ≥99.0%) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. All chemicals were used without further purification.

[0039] Janus-C 3 N 5 Preparation

[0040] Janus-structured C was prepared by gas template-assisted thermal polymerization. 3 N 5 In a standard procedure, 3.0 g of 1H-1,2,4-triazole-3-thiol (3-ST) and 15.0 g of ammonium chloride were manually ground for 30 min. The mixed precursors were transferred to a covered ceramic crucible (200 mL) and calcined at 550 °C for 4 h. The obtained product was named Janus-C 3 N 5 In addition, Janus-C with different calcination times (1 hour, 2 hours, and 3 hours) was prepared. 3 N 5 To study the synthesis mechanism, these samples are denoted as Janus-C 3 N 5 -1h, Janus-C 3 N 5 -2h and Janus-C 3 N 5 -3h. Bulk gC 3 N 4 and bulk gC 3 N 5 The preparation of melamine was as follows: 10 g of melamine was directly heated to 550 °C for 4 h in a covered ceramic crucible (200 mL) (heating rate, 2.3 °C min -1 The obtained product was designated as bulk gC 3 N 4 and bulk gC 3 N5 .

[0041] feature

[0042] The bulk-C samples were observed using a transmission electron microscope (TEM, JEM-2010EX, 200 kV) and a scanning electron microscope (SEM, S4800, 5 kV, 10 μA). 3 N 4 、bulk-C 3 N 5 and Janus-C 3 N 5 The chemical structure was characterized by powder X-ray diffraction (XRD, Smartlab TM 9KW, Cu Kα radiation, λ = 0.154178nm), X-ray photoelectron spectroscopy (XPS, Al KαX-ray source, ULVAC-PHI), 13C solid-state nuclear magnetic resonance (NMRC, Bruker avance III 400MHz) and Fourier transform infrared measurement (FTIR, Nicolet Nexus 470). XPS combined with ion beam etching method (0 seconds, 15 seconds, 30 seconds) was used to characterize Janus-C 3 N 5 and bulk-C 3 N 5 The chemical structure of bulk C was analyzed in depth using the BELSORP-MINI instrument at 77K. 3 N 4 , Block C 3 N 5 and Janus-C 3 N 5 The porosity information of bulk C was analyzed by steady-state photoluminescence spectroscopy (PL, F-4600FL), time-resolved photoluminescence decay spectroscopy (FLS920), ultraviolet-visible diffuse reflectance spectroscopy (UV-visDRS, Perkin-Elmer Lambda 35 spectrophotometer, 200nm-800nm) and electron paramagnetic resonance spectroscopy (BrukerESR JESFA200 spectrometer). 3 N 6 , Block C 3 E 5 and Janus-C 3 N 5 Photogenerated charge separation performance. Defect information capture measurements were collected using a Bruker ESR JESFA200 spectrometer. Thermogravimetric analysis (TG-DSC) was performed using a Netzsch STA449F3 (Ar flow).

[0043] Evaluation of photocatalytic hydrogen production activity

[0044] The photocatalytic hydrogen evolution rates (HERs) of different samples were tested in an online test system (Beijing Perfect Light Technology Co., Ltd., 300 W xenon lamp, λ ≥ 420 nm). Initially, 0.05 g of photocatalyst was dispersed in 100 mL of triethanolamine aqueous solution (10 vol%). Then platinum (3 wt%) was loaded onto the surface of the photocatalyst by photodeposition. 2 After purging for 30 minutes, the system was irradiated with a 300 W xenon lamp equipped with a 420 nm cutoff filter. The hydrogen evolution rate over time was analyzed using an online gas chromatograph (GC 9890A, TCD, argon). The following equation was used to calculate the H evolution rate at 420 nm and 450 nm: 2 Apparent quantum yield (AQY) of precipitation:

[0045]

[0046] DFT calculations

[0047] The entire calculation was performed using a spin-unrestricted DFT framework and implemented with the DMol3 module in the Materials Studio software. The exchange and correlation models were specified using the Perdew-Burke-Ernzerhof (PBE) functional in the generalized gradient approximation (GGA), and the dual numerical plus polarization (DNP) basis set was employed to describe the atomic orbitals.

[0048] Results Analysis

[0049] Janus-C 3 N 5 The preparation process of Figure 1 (a) and Figure 2 During the heat treatment, two different reaction pathways can occur: NH 4 Rapid pyrolysis of Cl and thermal copolymerization of 1,2,4-triazole-3-thiol. Gaseous byproducts (NH 4 NH produced by decomposition of Cl 3 and HCl) as gas templates to promote the thermal polycondensation reaction to form a nitrogen-rich triazole C 3 N 5 At the same time, as the polymerization proceeded, the gas template also mediated another set of thermal condensation reactions, leading to the formation of carbon-rich triazole-based C with nanosheet morphology. 3 N 5 structure. Ultimately, a layer of ultrathin nanosheets is formed on the honeycomb network. These morphological differences are attributed to the differences in the reaction temperature regions of the various reaction chains, which can be demonstrated by SEM and XRD analysis of samples subjected to different heat treatment times. Figure 3As shown in Figure 2, the coverage of the nanosheets on the honeycomb network surface increases with the heating time and reaches a maximum value when the precursor is completely reacted. 3 N 5 ,like Figure 4 As shown, samples at 1 hour, 2 hours, 3 hours and 4 hours are shown. As a result, Janus-C 3 N 5 The Janus structure is characterized by large ultrathin nanosheets (smooth side) and a honeycomb network (rough side). This Janus structure has a well-defined and ordered interface, which is further confirmed by TEM and HAADF imaging results ( Figure 1 (b)-(f)). The honeycomb network is composed of small nanosheets and contains many larger holes. Interestingly, EDX line scan results show that Janus-C 3 N 5 There are two distinct structural regions, characterized by a carbon-rich region and a carbon-poor region, corresponding to two different morphologies.

[0050] Janus-C was analyzed by XRD and FT-IR. 3 N 5 and bulk-C 3 N 5 structural characteristics. Figure 5 (a) shows that bulk-C 3 N 5 Two different diffraction peaks are shown at 13.5° and 27.9°, corresponding to the in-plane repeating unit (100) and the interlayer stacking unit (002), respectively. 3 N 5 The (002) and (100) reflections show a slight shift to lower angles and broader peaks, indicating a more compact interlayer spacing and a broadened in-plane periodicity. Figure 5 (b)-(d)) show that the bulk C 3 N 5 and Janus-C 3 N 5 At 3000-3500cm -1 1100-1700cm -1 and 810cm -1 The area shows the same block C 3 N 4 These peaks correspond to the residual -NH 2 / -OH groups, CN heterocycles in triazine, and CN heterocycles within the triazine moiety. 3 N 5 and Janus-C3 N 5 In 774cm -1 、1348cm -1 and 1618cm -1 The new peak observed at 889 cm -1 The peak intensity of 807cm -1 The peak value of C 3 N 5 The triazole part replaces the triazine part ( Figure 5 (c). Due to the overlapping vibration modes, the vibrations associated with the CN bonds in the triazole moiety are difficult to distinguish. 3 N 5 , with bulk-C 3 N 5 Compared with the TEM and SEM analysis, the intensity of the new peak decreased, indicating that the triazole part was partially degraded. 3 N 5 The rough side of the PDMS contains less C component (triazole part), while the smooth side contains more C component, although there is some triazole degradation ( Figure 1 (a) and (b)). In addition, with block C 3 N 4 and block C 3 N 5 In comparison, Janus-C 3 N 5 At 3000-3500cm -1 The peaks in the range shift to higher wavenumbers and increase in intensity, indicating enhanced hydrogen bonding, which may have a positive effect on the separation of photogenerated electron-hole pairs. 3 N 5 Static water contact angle measurements at different times further confirmed the Janus structure ( Figure 6-8 ).

[0051] Fig. 9 The X-ray photoelectron spectroscopy (XPS) measurement spectrum is shown, confirming that the bulk C 3 N 5 and Janus-C 3 N 5 Mainly composed of carbon (C), nitrogen (N) and oxygen (O). 3 N 5 High-resolution C1s spectra ( Fig.10 ) shows three different peaks at 284.6, 286.0 and 287.9 ​​eV, corresponding to CC bonds, NC=N groups and C-NHx groups, respectively. 3 N5 The N1s spectrum of the ions shows peaks at 398.4, 400.0 and 401.1 eV, which are attributed to CN=C, N-(C) 3 and N-Hx groups. It is worth noting that, compared with the bulk C 3 N 4 (287.6eV) compared to bulk C 3 N 5 The peak at 287.9 ​​eV shows a higher binding energy, while the peaks at 398.4 and 400.0 eV show that the 3 N 4 These changes indicate that the electronic coupling between CN or C=N bonds is stronger, which may be due to the introduction of triazole moieties, which enhances the electron absorption ability of carbon atoms by increasing the nitrogen content.

[0052] Block C 3 N 5 XPS depth profile of Fig.10 and Fig.11 ) show that the surface composition of C and N and the relative percentages and positions of C1s and N1s peaks change little during Ar ion etching. This stability indicates that bulk-C 3 N 5 The consistent nitrogen-rich triazole carbon nitride structure is maintained. 3 N 5 XPS depth analysis of the samples showed distinct behaviors. Before etching (0s), three fitting peaks were observed at 284.6, 286.1, and 287.8 eV. 3 N 5 Compared with the peak at 287.9 ​​eV, the peak at 287.8 eV has a lower binding energy, while the peak at 284.6 eV has a higher relative percentage (20.1% vs. 14.5%). As etching proceeds, the relative percentages of C and N at 284.6 eV decrease from 53.1 wt% to 51.4 wt% and from 20.1 at% to 18.1 at%, respectively. In contrast, the relative percentage at 398.4 eV increases from 77.4 at% to 78.5 at%. These findings are consistent with the FT-IR, TEM, and SEM results ( Figure 1 and Figure 5 ), indicating that as the carbon-rich nanosheets are etched, the C and N contents approach those of bulk C 3 N 5 The carbon-rich character is attributed to the partial destruction of the triazole moiety, leading to the formation of a π-conjugated structure, such as Figure 5 In addition, bulk-C 3 N 5and Janus-C 3 N 5 Solid-state NMR spectra ( Figure 5 (h)) at 156.7 and 164.6 ppm (attributed to C in the Melham unit 2 N-NH x (α) and C 3 N(β)) and 111.9 ppm (attributed to CHN-C(H)=N(δ) in the triazole unit). Janus-C 3 N 5 The new peak at 104.3 ppm corresponds to the carbon-rich motif (γ). The slight shift of the NMR signals of C(α), C(β), and C(δ) to higher fields is due to the increased shielding effect of the adjacent CC groups. These results indicate that Janus-C 3 N 5 Two different morphologies are shown: the nanosheet region is mainly carbon-rich and triazole-based, while the honeycomb network is mainly nitrogen-rich and triazole-based. The Janus structure facilitates the formation of well-defined homojunctions at the interface of these different carbon nitride structures.

[0053] The Janus homojunction C 3 N 5 The influence of physical structure, visible light absorption and charge carrier transfer pathways. Fig.12 (a) shows that all samples exhibit H 3 The IV isotherm of the hysteresis loop indicates that C 3 N 5 Stacked holes formed within the fragments. In these samples, Janus-C 3 N 5 The volume expansion is the largest, and the pore size distribution is larger than bulk-C 3 N 4 and bulk-C 3 N 5 narrow( Fig.12 (a) and (b)). This phenomenon is attributed to C 3 N 5 A unique stacking arrangement of fragments with a honeycomb network dispersed on the nanosheet surface. Fig.12 (b) shows that for bulk-C 3 N 4 、bulk-C 3 N 5 and Janus-C 3 N 5 The EPR signal intensity increases when the g value is 2.004, indicating that Janus-C 3 N 5The presence of unpaired electrons on the sp2 carbon atoms in the Fig.12 In (c), due to the n–π* electronic transition induced by the triazole group, the bulk-C 3 N 5 and Janus-C 3 N 5 It shows a clear absorption band around 500nm. Janus-C 3 N 5 It shows a higher absorption intensity at 500 nm, which can be attributed to the enhanced n–π* transition promoted by the homojunction. 3 N 4 、Block C 3 N 5 and Janus-C 3 N 5 The band gap energy (Eg), valence band potential (VB) and conduction band potential (CB) of g ) 1 / 2 ); VB and CB values ​​are 1.32eV, 0.83eV and 0.79eV respectively (E g =CB-VB); the Mott–Schottky spectrum values ​​are −1.21 eV, −0.89 eV, and −0.99 eV, respectively. Fig.12 (f) shows that Janus-C 3 N 5 The work function of (5.43 eV) is similar to that of bulk C 3 N 5 The photoluminescence (PL) intensity and resistance values ​​obtained from the EIS-Nquist plots follow the bulk-C 3 N 4 >bulk-C 3 N 5 >Janus-C 3 N 5 The photocurrent intensity follows the Janus-C 3 N 5 >bulk-C 3 N 5 >bulk-C 3 N 4 In addition, Janus-C 3 N 5 exhibited the longest photogenerated carrier lifetime (1.68ns, Fig.13 ). These results indicate that Janus-C 3 N5 The structure significantly improves the efficiency of photogenerated charge separation, indicating that it exhibits excellent photocatalytic activity. The interaction between the carbon-rich triazole-based nanosheets and the nitrogen-rich triazole-based honeycomb network leads to charge transfer due to the difference in Fermi levels, thus forming an internal electric field (IEF) that promotes efficient charge carrier separation.

[0054] Using platinum (3 wt%) as a promoter and triethanolamine (10 vol%) as a sacrificial agent, bulk C 3 N 4 , Block C 3 N 5 and Janus-C 3 N 5 The hydrogen evolution efficiency. Fig.14 As shown in (a), Janus-C 3 N 5 The HER was 1712.4 μmol h- 1 g- 1 , about bulk-C 3 N 5 (306.8 μmol h- 1 g- 1 ) is 5.58 times that of bulk-C 3 N 4 (121.2 μmol h- 1 g- 1 ) is 14.1 times. 3 N 5 The apparent quantum yields (AQY) at 420 nm and 500 nm are 2.8% and 0.5%, respectively. Fig.14 (b)). These AQY values ​​are consistent with their UV-Vis absorption spectra, indicating that the generation of hydrogen is mainly driven by photogenerated electrons. In addition, in contrast to most reported C-based 3 N 5 Compared with the photocatalyst Janus-C 3 N 5 Under similar illumination conditions, it exhibits excellent HER performance ( Fig.14 (d)). It is worth noting that Janus-C 3 N 5 Stable HER activity was maintained over four cycles of photocatalytic testing, showing minimal decay in hydrogen productivity.

[0055] Density functional theory (DFT) was used to study the 3 N 5 The relationship between the electronic and chemical structures of the variants. 3 N 5 (CC3 N 5 ), nitrogen-rich C 3 N 5 and their complexes (CN-C 3 N 5 ), the bottom of the conduction band and the top of the valence band are mainly occupied by carbon and nitrogen, respectively. 3 N 5 The impurity energy level near the bottom of the conduction band is shown, resulting in different band potentials between samples. 3 N 5 In comparison, CC 3 N 5 The calculated work function (Φ) and Fermi level (Ef) of CN-C are higher, which indicates that the Φ and Ef values ​​are balanced. The changes in band position and Φ promote the 3 N 5 The formation of a built-in electric field. Fig.15 As shown, NC 3 N 5 The charges generated in the ion source (lower Φ) migrate to the CC with higher Φ driven by the inherent potential difference. 3 N 5 region until equilibrium is reached. This results in CC 3 N 5 and NC 3 N 5 The built-in field (BIF) is formed between them. Differential charge density analysis ( Figure 16-18 ) confirms this charge redistribution at the homojunction interface, consistent with the observed work function differences. 3 N 5 and CN-C 3 N 5 The construction of homojunction leads to efficient charge separation and redistribution, which is crucial for improving the photocatalytic activity.

[0056] Based on the analysis of characterization, photocatalytic activity and DFT calculation results, CC 3 N 5 and NC 3 N 5 Homojunction charge transfer process between Fig.19 (g)). When CC 3 N 5 and NC 3 N 5 When in close contact, CC 3 N 5 The charges in the 3 N 5 , until their Fermi levels reach equilibrium. Due to charge rearrangement, this process forms a3 N 5 To NC 3 N 5 The built-in electric field of CC 3 N 5 The energy band of NC is bent upward (due to electron loss). 3 N 5 The energy band of CN-C is bent downward (due to electron accumulation). 3 N 5 These characteristics make CN-C 3 N 5 It can promote faster and more efficient directional transfer of photogenerated electrons and significantly improve its photocatalytic performance.

[0057] In summary, a new Janus homojunction C was constructed using a gas template-mediated strategy. 3 N 5 Extensive experimental and theoretical analysis showed that the optimized catalyst Janus-C 3 N 5 The Janus-C nanosheets exhibit two different morphologies: ultrathin nanosheets (smooth side) and honeycomb networks (rough side). The nanosheets are mainly composed of carbon-rich triazole carbon nitride, while the honeycomb networks are mainly composed of nitrogen-rich triazole carbon nitride. This configuration leads to an enhanced internal electric field (IEF) between these different structures. Under visible light irradiation, Janus-C 3 N 5 H 2 The precipitation rate reached 1712.4 μmol h- 1 g- 1 , than block C 3 N 5 (306.8 μmol h- 1 g- 1 ) is about 5.58 times higher than that of bulk C 3 N 4 (121.2 μmol h- 1 g- 1 ) is 14.1 times higher. Janus-C 3 N 5 The AQY at 420 nm and 500 nm were estimated to be 2.8% and 0.5%, respectively.

Claims

1. A C3N5 photocatalyst having a Janus homogeneous structure, characterized in that: The photocatalyst is composed of nitrogen-rich carbon nitride and presents a structure combining a honeycomb network and a nanosheet form, with stacked holes inside.

2. The C3N5 photocatalyst having a Janus homogeneous structure according to claim 1, characterized in that: The nitrogen-rich carbon nitride is a nitrogen-rich triazole group.

3. The C3N5 photocatalyst having a Janus homogeneous structure according to claim 1, characterized in that: The photocatalyst forms a homojunction at the interface of the nanosheets and the honeycomb network.

4. The C3N5 photocatalyst having a Janus homogeneous structure according to claim 1, characterized in that: The honeycomb network is a rough side, and the nanosheet is a smooth side.

5. The C3N5 photocatalyst having a Janus homogeneous structure according to claim 1, characterized in that: The honeycomb network is mainly composed of nitrogen-rich and triazole groups, and the nanosheet is mainly composed of carbon-rich and triazole groups.

6. The method for preparing the C3N5 photocatalyst having a Janus homogeneous structure according to claim 1, characterized in that: The following steps are involved: Step 1: Grind and mix triazole mercaptan and ammonium chloride, and rapidly pyrolyze the ammonium chloride to obtain a photocatalyst precursor; Step 2: Transfer the photocatalyst precursor obtained in step 1 to a covered ceramic crucible for calcination.

7. The method for preparing the C3N5 photocatalyst according to claim 6, characterized in that: In the step 1, the triazole thiol is 1H-1,2,4-triazole-3-thiol (3-ST), and the added amount is 1-5g; 10-20g of ammonium chloride is added, and the grinding time is 20-40min.

8. The method for preparing the C3N5 photocatalyst according to claim 4, characterized in that: In the step 2, the calcination conditions include: the heating rate of the calcination temperature is 1-3℃min -1 , the temperature is 500-600°C, and the calcination time is 1-5h, preferably 4h.

9. Use of the C3N5 photocatalyst with Janus homogeneous structure as claimed in claim 1 in energy conversion and photocatalysis.

Citation Information

Patent Citations

  • Carbon nitride homojunction photocatalyst and preparation method and application thereof

    CN111450864A

  • Carbon nitride composite photocatalyst as well as preparation method and application thereof

    CN115445646A

  • Preparation and application of S-type crystallized carbon nitride homojunction photocatalytic material

    CN115463682A

  • Photochargeable homojunction electrode based on water-soluble carbon-rich carbon nitride polymer and preparation method and application thereof

    CN115621053A

  • High-crystallinity CN homojunction photocatalyst as well as preparation method and application thereof

    CN117324018A